Ultra Structure of the Antennal Sensilla of the Fruit Fly Bactrocera carambolae (Insecta: Diptera: Tephritidae) - Anila, Manoj; Azirun M, Sofian (Malaysian Journal of Science, 2002)
The antennal sensilla of Bactrocera caraznbolae (Diptera: Tephritidae) were examined using Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM). SEM has revealed, morphologically three main types and five sub types of antennal sensilla. The main types are niicrotrichia (m) having longitudinal cleft, sensilla chaetica (ch) and sensilla basiconica (Sb). The two types of sensilla basiconica observed and identified were multiporus double walled sensilla (MpDs) and multiporus single walled sensilla (MpSs) together with its own three sub types; innervated with 1 to 2 sensory cells (S1) and innervated with 2 to 4 sensory cells (S2) and MpSs having pimping on the cuticular surface (S3). Microtrichia was found distributed along the whole length of the antennae with its density more in the hiniculus and probably functions as mechanoreceptors. MpDs having thick wall and lesser number of pores must be regarded as tactile in functions and MpSs having thin membranous wall and numerous pores are usually regarded as receptors of taste and odour. MpDs and MpSs were distributed among the microtrichia on the fliniculus alone. Sensilla chaetica (ch) were seen only on the scape and pedicel, which probably functions as tactile receptors. One sensory pit on the funiculus and 2 to 3 antennal cuticular pores on the pedicel were observed. These results are compared with previously published studies on Tephritidae.